A Perspective on the Overarching Role of Hydrogen, Ammonia, and Methanol Carbon-Neutral Fuels towards Net Zero Emission in the Next Three Decades - Haifeng Liu; Jeffrey Dankwa Ampah; Yang Zhao; Xingyu Sun; Linxun Xu; Xueli Jiang; Shuaishuai Wang (Energies, 2022)
Arguably, one of the most important issues the world is facing currently is climate change. At the current rate of fossil fuel consumption, the world is heading towards extreme levels of global temperature rise if immediate actions are not taken. Transforming the current energy system from one largely based on fossil fuels to a carbon-neutral one requires unprecedented speed. Based on the current state of development, direct electrification of the future energy system alone is technically challenging and not enough, especially in hard-to-abate sectors like heavy industry, road trucking, international shipping, and aviation. This leaves a considerable demand for alternative carbon-neutral fuels such as green ammonia and hydrogen and renewable methanol. From this perspective, we discuss the overarching roles of each fuel in reaching net zero emission within the next three decades. The challenges and future directions associated with the fuels conclude the current perspective paper.